The Causes of Informal Elderly Care at Home: a Look at the Caregivers‘ Experience - Junevičienė, Jolita (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]The topic of informal care is relevant in our country, because Lithuania is outstanding for being a country where population ageing is one of the fastest in the European Union and emigration of working-age population is very high. Moreover, traditional family ties are still strong in Lithuania. The aim of this article is to reveal the causes of informal elderly care at home. The analysis of causes is based on the experience of informal caregivers. Data for the research was obtained from 20 semi-structured interviews with informal carers. The method of qualitative content analysis was used for data analysis. The carried out research confirms the complexity of the relationship between an elderly person in need of care and an informal caregiver and reveals the variety of informal care causes. It turned out that the decision to take care of a close elderly at home is determined not only by social aspects such as the feeling of children’s duty, no-confidence in institutional care, but also by economic aspects such as expensiveness of formal care services, the assessment of nursing benefit as an additional source of income.
Keywords: informal care, the elderly, caregivers‘ experience, the informal care model, causes of care at home